School administration and its role in the mathematical creativity of physical education teachers for some Some primary schools in Lattakia Governorate from the point of view of physical education teachers - سلمان, ندى; خلود علي ديب,; رشا صقر , (Latakia University Journal -Medical Sciences Series, 2023)
This study aims to reveal the role of the school administration in the mathematical creativity of physical education teachers for some basic and secondary education schools in Lattakia Governorate, and to identify the difference in the role of the school administration in the mathematical creativity of physical education teachers according to the variables of the type of schools (primary, secondary education), gender, years of teaching for teachers .The researcher used the descriptive method in the survey method due to its suitability to the subject of the study. The researcher designed a questionnaire consisting of (33) items. The sample of the study was randomly selected from physical education teachers in Lattakia Governorate. The sample was male and female teachers of some secondary schools in Lattakia Governorate. The researcher is a teacher or teacher from each school. And they obtained (58) questionnaire subject to statistical analysis, and the study concluded that there is an effective and important role for the school administration in the mathematical creativity of physical education teachers for some schools (primary and secondary education) in Lattakia Governorate, in addition to the existence of statistically significant differences between the arithmetic circles according to The variable of the type of schools (primary and secondary education) and the variable of teaching years for the mathematical creativity of physical education teachers, and working on the possibility of activating the role of mathematical creativity for physical education teachers in schools (primary and secondary education).